Plant Electrophysiology Methods and Cell Electrophysiology - Volkov, Alexander G. (Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book, written by the leading scientists in the field of plant electrophysiology, provides a comprehensive and up-to-date overview of single-cell electrophysiology and current methods in plant electrophysiology. The first part begins with a historical introduction to plant electrophysiology. Chapters describe methods of measuring the membrane potentials, ion fluxes, trans-membrane ion gradients, ion-selective microelectrode measurements, the patch-clamp technique, multi-electrode arrays, electrochemical impedance spectroscopy, data acquisition, and electrostimulation methods. The second part deals with plant cell electrophysiology, including chapters on the electrophysiology of Characean cells, functional characterization of plant ion channels, and mechanisms of passive permeation of ions and molecules through plant membranes.